From voluntary to mandatory corporate accountability: The politics of the German Supply Chain Due Diligence Act - David Weihrauch; Sophia Carodenuto; Sina Leipold (Regulation & Governance, 2022)
Following a long-standing and highly contested policy debate, in June 2021, the German parliament passed the Supply Chain Due Diligence Act requiring mandatory due diligence (MDD) of large companies, holding them accountable for the impacts of their supply chain operations abroad. Applying the discursive agency approach and using evidence from policy documents and 21 interviews with key stakeholders, we analyze the political strategies that paved the way toward MDD in Germany. The decisive strategy was an innovative benchmarking and monitoring mechanism that provided the legitimacy for a law and opened a window of opportunity for MDD supporters. Civil society and supportive politicians used this window of opportunity to build broad political coalitions that included the support of some companies. We discuss the ramifications of these findings for understanding the domestic politics behind the newly emerging norm of foreign corporate accountability.
Keywords: 330; discursive agency; foreign corporate accountability; Germany; human rights; mandatory due diligence